Are the Hot IPOs Still Relevant? Evidence from China's Growth Enterprise Market - Yang, Lu; Zhang, Huimin; Hamori, Shigeyuki (Journal of Reviews on Global Economics, 2015)
This paper investigates whether the hot IPO effect persists post-IPO in China's Growth Enterprise Market (GEM) based on the dynamic equicorrelation of trading volume and stock returns. We find that the hot IPO effect ends after two years with the imbalance between demand and supply for GEM stock relieved, which indicates that the rational learning process requires almost two years for most investors. Further, we confirm that returns and volumes are positively correlated at the 1% significance level. This result indicates that the fundamental analysis may not apply to the GEM because the information content of trading volume is capable of forecasting stock returns.